(untitled) (Al-Aasar, 2025)
This study presents a comparative analysis of Allama Iqbal’s philosophy of Khudi (Selfhood) and the concepts of contemporary psychological philosophy, aiming to elucidate the evolutionary, moral, spiritual, and creative dimensions of human personality. In Iqbal’s concept of Khudi, self-awareness, willpower, moral consciousness, and spiritual awakening occupy a central position, guiding an individual toward the development of creative capacities, personal and social responsibilities, and intellectual and practical autonomy. The study highlights that the philosophy of Khudi is indispensable not only for personal growth but also for social reform and cultural consciousness.The research analyzes fundamental concepts of modern psychological philosophy such as individuality, self-realization, consciousness, personality development, and inferiority complex in the light of Iqbal’s philosophy of Khudi. In Iqbal’s framework, the awakening of Khudi empowers an individual with moral and spiritual responsibility, whereas contemporary psychological philosophy emphasizes the psychological and cognitive aspects that foster personality, creative potential, and intellectual capacities.The study examines both similarities and differences between Iqbal’s concept of Khudi and modern psychological philosophy. The similarity lies in their focus on self-awareness, personal development, and creative potential, while the difference is that Iqbal stresses a spiritual and moral dimension, whereas modern psychological philosophy predominantly addresses the psychological, cognitive, and social dimensions of the individual.Furthermore, the study explores the contemporary significance of Khudi in moral development, intellectual training of the youth, its utility in educational systems, and its role in social reform. The findings suggest that Iqbal’s philosophy of Khudi provides a comprehensive and practical framework for personal, ethical, social, and cultural development.